Long-Term Outcomes of a Brief Emotion-Focused Family Therapy Intervention for Eating Disorders Across the Lifespan: A Mixed-Methods Study (Canadian Journal of Counselling and Psychotherapy, 2020)
Emotion-focused family therapy (EFFT) empowers caregivers to support their loved one’s eating disorder (ED) recovery. Data were collected over time from 74 caregivers who participated in a 2-day EFFT workshop. Results revealed positive outcomes related to self-efficacy, treatment engagement fears, and the accommodation and enabling of behaviours. A thematic analysis of interviews conducted with eight caregivers identified the following themes: (a) increasing self-efficacy with emotion, (b) working through emotion blocks, (c) strengthening interpersonal relationships, (d) experiencing togetherness among participants, and (e) benefiting from experiential practice via role-play. Results suggest this brief intervention is associated with positive caregiver outcomes that can be maintained over time.